2006
DOI: 10.1111/j.1532-950x.2006.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of the Zurich Cementless Total Hip Acetabular Component

Abstract: Dogs with lucency in > or =2 zones of analysis should be evaluated more frequently for clinical signs of implant loosening. Further investigation of serial radiographs after ZCTH arthroplasty is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 17 publications
1
45
2
3
Order By: Relevance
“…Yee et al [12] and Hanson et al [3] have reported that the development of cementless prostheses was based on high rates of aseptic loosening, particularly of the acetabular component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yee et al [12] and Hanson et al [3] have reported that the development of cementless prostheses was based on high rates of aseptic loosening, particularly of the acetabular component.…”
Section: Discussionmentioning
confidence: 99%
“…Lasting and rigid fixation of the acetabular cup without cement has been demonstrated in dogs [3,21]. Different types of prosthetic acetabular cups have been successfully used, such as the press-fit, the threaded, and the screwed models [3,12,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A avaliação pós-operatória das artroplastias é imprescindível na determinação do posicionamento dos componentes protéticos e na detecção precoce de potenciais complicações (Young e Schiller, 1992;Hanson et al, 2006). Tal avaliação, normalmente realizada por meio de exame radiográfico, de fato possibilita a visibilização da maioria das complicações secundárias ao procedimento de artroplastia total coxofemoral, mesmo aquelas de início assintomático ou muito lento, tais como retroversão da haste femoral, falhas de preenchimento do canal medular femoral, áreas de radioluscência tanto em região do cimento ósseo quanto na interface entre o osso e os implantes, e afundamento da haste femoral no canal medular (Young e Schiller, 1992;Palmisano et al, 2003;Bergh et al, 2006).…”
Section: Discussionunclassified
“…O estudo dessas linhas nas interfaces dos implantes é fundamental para se predizer a soltura ou o afrouxamento dos componentes protéticos (Bergh et al, 2004;Hanson et al, 2006;Suh et al, 2013) e, uma vez que a tomografia computadorizada se mostre mais específica na sua determinação (Suh et al, 2013), assim como verificado no presente estudo, pode-se considerá-la vantajosa em relação ao exame radiográfico.…”
Section: Discussionunclassified
See 1 more Smart Citation